The Bishop’s Warmian Landvogt`s Court in Lidzbark in the years 1773-1838 - Ornatek, Adam (Prawo Kanoniczne, 2026)
This article examines the legal regulations governing administration within the dominial territory of the Diocese of Warmia in civil and criminal matters (in civilibus et criminalibus). Jurisdiction in these matters was exercised by the diocesan bishop and the Warmian Cathedral Chapter under the sovereignty of the Kingdom of Poland and, following annexation, within the Kingdom of Prussia. King Frederick II supported the establishment of a legal order in this jurisdiction, modelled on the system introduced after the incorporation of Silesia into his monarchy. To this end, he established the Episcopal Warmian Landvogt’s Court in Lidzbark and promulgated its regulations. The absolutist monarch permitted the continuation of patrimonial judicature, which derived from the centuries-old dominial structure of the Diocese of Warmia.